Research Hotspot and Trend Analysis of Earth-Rockfill Dam Stability Based on Knowledge Map - WANG Luoxi; HAN Peifeng; LI Yan'ang; YANG Guocheng; QIU Hongzhi (Renmin Zhujiang)
Since the 20th century, earth-rockfill dam instability accidents have occurred frequently all over the world. In order to systematically summarize the current status and hotspots of research on earth-rockfill dam stability and analyze the future development trend of earth-rockfill dam stability, this paper sorted out the factors of earth-rockfill dam instability found by Chinese and foreign scholars and carried out a comparative analysis. Since The instability modes of earth-rockfill dams are complex and varied, the research on the different instability modes of earth-rockfill dams by Chinese and foreign scholars was summarized. In terms of theoretical calculation, the calculation models developed by Chinese and foreign scholars for the instability of earth-rockfill dams were systematically sorted out, and the applicability of different calculation models was compared. In order to quantitatively and visually analyze the research hotspots and trends of Chinese and foreign scholars on the instability of earth-rockfill dam, CiteSpace was used to analyze 1 197 papers on the stability of earth-rockfill dam in CNKI and Web of Science in the past 15 years from 2009 to 2023, and the research dynamics of the field in the past 15 years were comprehensively and visually analyzed according to the author groups, research institutions, and keyword clustering. The development trend of the existing research, as well as the related problems and future research work, were discussed and prospected from a macro perspective. The future research direction of the stability of earth-rockfill dams, as well as the difficulties and hotspots of the current research were summarized.